Fodder Distribution Operations as Sustainable Economic Progress in Semi-Urban Areas - Ray, A. K.; Datta, Dhananjoy (Indian Journal of Marketing, 2013)
The livestock is a sub-sector of the agricultural sector, which adds almost 32% of agricultural output in India. India assists 20% of the livestock population of the world, covering 2.3% geographical area. Recent population trends of India are not matching with the required trend of livestock growth rate due to various reasons, which signifies that India would have to import milk by 2021 and price negotiation could be a problem, if the milk production does not increases at the rate of 5.5% to 180 million tonnes. For economic and sustainable livestock, it is essential to understand the significance of fodder as sustainable produce in the peri-urban areas because semi urban livestock farming and promising fodder bazaars are pointers of rapidly shifting economic circumstances in the livestock sub-sector. This signifies smooth supply of fodder for sustainable livestock population. The present study is an attempt to integrate fodder with sustainable developmental approaches, which includes examining various fodder related objectives. This objective involved analyzing fodder distribution channels in fodder retailing, price margin between the different points of channels, and women's participation in fodder retailing. In this study, data was collected from primary and secondary sources. For collecting primary data, three peri-urban areas - Kolkata in West Bengal, Guwahati in Assam and Agartala in Tripura were considered for the study. The total sample size was 480 respondents, which included producers, retailers or traders, commission agents, and consumers of fodder. The respondents were interviewed randomly in the study area with the help of a structured interview schedule. Simple statistical analysis like percentage analysis was used to achieve the objectives of the study. The expected outcomes of the study are a pre-requisite for sustainable development of semi urban economy related to improvement of producers' share in consumers' rupee, elimination of the middlemen menace, participation of women in fodder retailing and eliminating credit and the price interlocking system.